Bird populations as sentinels of endocrine disrupting chemicals - Claudio Carere; David Costantini; Alberto Sorace; Daniela Santucci; Enrico Alleva (Istituto Superiore di Sanità, 2010)
Exposure to endocrine disrupting chemicals (EDCs) is a widespread phenomenon in nature. Although the mechanisms of action of EDCs are actively studied, the consequences of endocrine disruption (ED) at the population level and the adaptations evolved to cope with chronic EDC exposure have been overlooked. Birds probably represent the animal taxon most successfully adapted to synanthropic life. Hence, birds share with humans a similar pattern of exposure to xenobiotics. In this article, we review case studies on patterns of behaviour that deviate from the expectation in bird species exposed to EDCs. We provide behavioural and ecological parameters to be used as endpoints of ED; methodological requirements and caveats based on species-specific life-history traits, behavioural repertoires, developmental styles, and possibility of captive breeding; a list of species that could be used as sentinels to assess the quality of man-made environment.